Fast-starting after a breath: Air-breathing motions are kinematically similar to escape responses in the catfish Hoplosternum littorale - Paolo, Domenici; Tommy, Norin; Peter, G. Bushnell; Jacob, L. Johansen; Peter, Vilhelm Skov; Morten, B. S. Svendsen; John, F. Steffensen; Augusto, S. Abe (My University, 2015)
Fast-starts are brief accelerations commonly observed in fish within the context of predator-prey interactions. In typical C-start escape responses, fish react to a threatening stimulus by bending their body into a C-shape during the first muscle contraction (i.e. stage 1) which provides a sudden acceleration away from the stimulus. Recently, similar C-starts have been recorded in fish aiming at a prey. Little is known about C-starts outside the context of predator-prey interactions, though recent work has shown that escape response can also be induced by high temperature. Here, we test the hypothesis that air-breathing fish may use C-starts in the context of gulping air at the surface. Hoplosternum littorale is an airbreathing freshwater catfish found in South America. Field video observations reveal that their air-breathing behaviour consists of airgulping at the surface, followed by a fast turn which re-directs the fish towards the bottom. Using high-speed video in the laboratory, we compared the kinematics of the turn immediately following airgulping performed by H. littorale in normoxia with those of mechanically-triggered C-start escape responses and with routine (i.e. spontaneous) turns. Our results show that air-breathing events overlap considerably with escape responses with a large stage 1 angle in terms of turning rates, distance covered and the relationship between these rates. Therefore, these two behaviours can be considered kinematically comparable, suggesting that airbreathing in this species is followed by escape-like C-start motions, presumably to minimise time at the surface and exposure to avian predators. These findings show that C-starts can occur in a variety of contexts in which fish may need to get away from areas of potential danger.
Keywords: Air-breathing; Behaviour; C-start; Escape response; Fish; Kinematics